Reflection in Pixels: Scrutinizing Students' Perspectives on Digital Reflective Journals - Dea Silvani; Santiana, Santiana; Sitti Syakira (Journal of English Education and Teaching, 2024)
Reflection plays an important role in language learning. Through reflection, students are encouraged to learn how to learn to acquire deeper learning. This study investigates students’ perceptions of digital reflective journals as a means of reflective practice in their ESP classroom. This study involved 45 students who enrolled in a Business English class where they were required to write reflective journals digitally at the end of the teaching and learning process. This study used questionnaires and semi-structured interviews as the instruments to collect the data. The quantitative data from the questionnaire were analysed with the assistance of SPSS to examine the frequency of students’ responses to each statement listed on the questionnaire. Meanwhile, the qualitative data from semi-structured interviews were analysed through the steps of data condensation, data display, and conclusion. The findings of this study revealed that students admitted to the beneficial roles of digital reflective journals. It helped them raise their self-awareness, and develop their critical and problem-solving skills. Besides, they also assumed that writing reflective journals digitally was more convenient because it offered ease of access and flexibility. Therefore, digital reflective journals can serve as valuable tools to improve the quality of language learning that can be considered to be utilized in language classrooms.